Comparative Genomics of Loigolactobacillus Coryniformis With an Emphasis on L. Coryniformis Strain FOL-19 Isolated From Cheese - Gumustop, Ismail; Ortakci, Fatih (Elsevier, 2023)
Loigolactobacillus coryniformis is a member of lactic acid bacteria isolated from various ecological niches. We isolated a novel L. coryniformis strain FOL-19 from artisanal Tulum cheese and performed the whole-genome sequencing for FOL-19. Then, genomic characterization of FOL-19 against ten available whole genome sequences of the same species isolated from kimchi, silage, fermented meat, air of cowshed, dairy, and pheasant chyme was performed to uncover the genetic diversity and biotechnological potential of overall species. The average genome size of 2.93 +/- 0.1 Mb, GC content of 42.96% +/- 0.002, number of CDS of 2905 +/- 165, number of tRNA of 56 +/- 10, and number of CRISPR elements of 6.55 +/- 1.83 was found. Both Type I and II Cas clusters were observed in L. coryniformis. No bacteriocin biosynthesis gene clusters were found. All strains harbored at least one plasmid except KCTC 3167. All strains were predicted to carry multiple IS elements. The most common origin of the IS elements was belong to Lactiplantibacillus plantarum. Comparative genomic analysis of L. coryniformis revealed hypervariability at the strain level and the presence of CRISPR/Cas suggests that L. coryniformis holds a promising potential for being a reservoir for new CRISPR-based tools. All L. coryniformis strains except PH-1 were predicted to harbor pdu and cbi-cob-hem gene clusters encoding industrially relevant traits of reuterin and cobalamin biosynthesis, respectively. These findings put a step forward for the genomic characterization of L. coryniformis strains for biotechnological applications via genome-guided strain selection to identify industrially relevant traits.
Keywords: Loigolactobacillus Coryniformis; Comparative Genomics; Crispr/Cas; Reuterin; Cobalamin